Perbandingan Kualitas Layanan Kefarmasian Di Puskesmas Berstandar ISO dan Non-ISO Kota Denpasar - Jaya, Made Krisna Adi; Dewi, Ni Luh Santiyani; Rudiartha, I Gusti Lanang Made (Jurnal Farmasi Udayana; Vol. 10, No 1, Tahun 2021DO - 10.24843/JFU.2021.v10.i01.p06, 2021)
Background: Primary Health Care (puskesmas in Indonesian) is a facilities/infrastructure used to improve health status and health development. Pharmaceutical services at puskesmas are always in the spotlight of the community and tend to be negative in stigma. The community paradigm, especially in Denpasar, tends to state that pharmaceutical services at ISO-standard puskesmas are better than non-ISO. However, this does not mean that non-ISO health centers in Denpasar City do not provide optimal services to the community. Based on this problem, research needs to be conducted to assess the extent of differences in the quality of pharmaceutical services in ISO and non-ISO health centers in Denpasar. Objective: This study aims to compare the quality of pharmaceutical services in ISO and non-ISO puskesmas including the waiting time for drug services, the incidence of Drug Related Problems (DRP), and the level of patient satisfaction. Methods : An analytic observational study was conducted by observing 184 respondents who used the health services at the puskesmas in Denpasar. Waiting time was observed from the patient submitting a prescription until getting the medicine; DRP was observed by the number of drug interactions, patient adherence to therapy and the incidence of Adverse Drug Reaction (ADR); and patient satisfaction using the satisfaction questionnaire. Results: The waiting time for drug services showed that the ISO puskesmas was superior to non-ISO (p <0.05) while the DRP incidence and patient-related satisfaction were not significantly different (p> 0.05). Conclusion: Non-ISO Puskesmas in Denpasar showed the quality of pharmaceutical services that were comparable to Puskesmas with ISO standards.   Keywords: Drug Services, Drug Related Problem, Patients Satisfaction, Primary Health Care